Bukhari group of companies - Damle, Shamkant, (SAGE Knowledge. Cases., 2017)
Kurla is a central suburb of Mumbai, which hosts a large number of scrap-dealers. Scrap-dealing in Kurla is not just a meeting point for rag-pickers. Even before the western world thought of recycling Kurla had become a hub for this business. Everything is dismantled in Kurla other than the scrapping and dismantling of ships which is done at Alang in Gujarat. Malad is north-western suburb, which is house to many BPOs. It was observed that the obnoxious gases from the Malad creek damaged the motherboards of thousands of computers in BPO and KPO industry, every year. These computers were then dismantled in Kurla silently. Car and TV dealers from all over India could offer replacement schemes only because of the support from the scrap-handling industry.